1981
DOI: 10.1007/bf00115077
|View full text |Cite
|
Sign up to set email alerts
|

An evaluation of the average superfluid density of 4He in a cylindrical pore near T λ predicted by the Ginzburg-Pitaevskii-Mamaladze theory

Abstract: A numerical evaluation of the average superfluid density of 4He in a cylindrical pore near T a predicted by the Ginzburg-Pitaevskii-Mamaladze theory has been carried out as a function of pore radius and temperature. The results are presented in graphical form and in terms of an accurately fitting closed algebraic form.The only detailed prediction for the behavior of the superfluid density ps of 4He in a cylindrical pore of which we know is provided by the free-energyexpansion theory of Ginzburg and Pitaevskii … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

1981
1981
1988
1988

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…The numerical coefficient k is found to depend slightly on the ratio £(T)/R and to vary between 2.2 and 2.7. The same problem has been treated for superfluid 4 He confined in cylindrical tube by Bot, Schubert, and Zimmermann, 9 who showed that the same depression of superfluid density is expected as given by Eq. (l) with /c=2.4.…”
mentioning
confidence: 72%
“…The numerical coefficient k is found to depend slightly on the ratio £(T)/R and to vary between 2.2 and 2.7. The same problem has been treated for superfluid 4 He confined in cylindrical tube by Bot, Schubert, and Zimmermann, 9 who showed that the same depression of superfluid density is expected as given by Eq. (l) with /c=2.4.…”
mentioning
confidence: 72%